Attitude and Strategies for Small Farmers in Facing Farm Risks: Case Study of Large Chili Farming in Lombok Island, Indonesia - Muhamad Siddik; Bambang Dipokusumo (Journal of Global Innovations in Agricultural Sciences)
This paper describes the types of risks, sources of risks, levels of risks, attitudes, and strategies of small farmers in dealing with the risks of large chili farming businesses on Lombok Island, Indonesia. Data collection used the triangulation method, a combination of structured interview methods with farmers, in-depth interviews with key informants, field observations, virtual surveys, and literature studies. Types of risks were analyzed descriptively; sources of risks were analyzed using FMEA; risk levels using the coefficient of variation; farmers' attitudes towards risk using regression and farmers' strategies in dealing with risks were analyzed descriptively, qualitatively and quantitatively. The study found that the types of farming risks faced by farmers are production risks and product price risks. The main sources of production risk are pest and disease attacks and climate change, while price risks come from the abundance of chili production. In dealing with production risks, farmers take a risk-taking attitude, while in dealing with price risks, farmers are neutral. One of the effective risk management strategies that supports the sustainability of large chili farming businesses on Lombok Island is cooperation between farmers and collectors and/or inter-island traders, this is what makes this study new because it is unique and has not been found in other farming businesses. Keywords: Coefficient variation, triangulation methods, large chili farm, Lombok Island, risk management.